A home away from home for adolescents: narratives on residential care life in eThekwini, KwaZulu-Natal, South Africa - Xolani Shabangu; Raisuyah Bhagwan; Fathima Dewan (Scottish Journal of Residential Child Care)
Residential care facilities play a significant role in accommodating orphaned and vulnerable children both in South Africa and internationally. However, there is scant information about the experiences adolescents have of residential care life in South Africa. This study explores the experiences of adolescents at a residential care setting, in the eThekwini region of KwaZulu-Natal, in South Africa. The study was conducted using a qualitative research methodology. Twenty-six participants were recruited using non-probability purposive sampling methods. Findings indicate that children in residential care have both positive and negative experiences of residential care. The findings that were significant highlighted adolescents’ emotions related to growing up in a residential care setting and key issues around the experiences of support and care within these settings. Two core themes were identified using thematic analysis. Firstly, the daily life experiences of growing up in the residential care facility, and secondly, their experiences of support and care therein. These findings are relevant to improving child care services at residential care facilities in South Africa and enabling the wellbeing of adolescents.